Can Competitiveness Predict Education and Labor Market Outcomes? Evidence from Incentivized Choice and Survey Measures - Buser, Thomas; Niederle, Muriel; Oosterbeek, Hessel (The Review of Economics and Statistics, 2026)
We assess the predictive power of two measures of competitiveness for education and labor market outcomes using a large, representative survey panel. The first is incentivized and is an online adaptation of the laboratory-based Niederle-Vesterlund measure. The second is an unincentivized survey question eliciting general competitiveness. Both measures are strong predictors of income, occupation, level of education, and field of study. The predictive power of the new unincentivized measure is robust to controlling for other traits, including risk attitudes, confidence, and the Big Five personality traits. For most outcomes, the predictive power of competitiveness exceeds that of the other traits.